Enhanced optical properties of β-Ga2O3-xSxS: A DFT study - G.B. Eshonqulov (22927297) (2025)
Gallium oxide (GaO) is a promising material for ultraviolet optoelectronic applications due to its desirable properties, such as a large band gap, decent charge mobility, and high breakdown electrical characteristics. By reducing the band gap of the material, its applicability can be extended beyond ultraviolet power applications. Here, we conduct systematic density functional theory calculations to study the effect of sulfur doping on the electronic and optical properties of β-Ga2O3. We find that the band gap of the material decreases with increasing sulfur content (from 4.81 eV to 1.59 eV), accompanied by symmetric shifts in both the valence-band offset and the conduction-band edge. Consequently, the absorption intensity in the visible and UV ranges of the spectrum increases by more than an order of magnitude, depending on the level of doping, with a clear red shift. The present predictive modeling can be useful for developing Ga2O3-based materials for optoelectronic applications. Other Information Published in: Physica B: Condensed Matter License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.physb.2025.417367